Poverty Transitions and the Near-Poor in the Philippines - Jose Ramon G. Albert (Philippine Institute for Development Studies (PIDS), 2023)
This study provides an in-depth analysis of poverty dynamics in the Philippines, focusing on the period from 2003 to 2009. Utilizing panel data from the Family Income and Expenditure Survey (FIES) to examine transitions into and out of poverty, it pays special attention to the near-poor population - those whose incomes hover just above the poverty line. Despite the Philippines experiencing an average growth of 4.8% in real Gross Domestic Product during this period, the overall poverty incidence remained stagnant, highlighting a disconnect between economic growth and poverty reduction. This phenomenon is partly attributed to the low Growth Elasticity of Poverty in the country, indicating that economic growth has not been sufficiently inclusive or propoor. The study delves into the characteristics of the poor and near-poor, revealing that these groups have similar profiles: they are predominantly located in rural areas and face vulnerabilities such as labor and employment shocks, price shocks, and natural disasters. The study also explores the socioeconomic dimensions affecting Filipino households, including family size, employment type, education levels, and exposure to natural and man-made disasters. A significant contribution of this research is its analysis of poverty spells and transitions using the FIES panel data. It uncovers that while some households have escaped poverty, others have fallen into it, with the near-poor being particularly susceptible to downward mobility. The study also discusses the resilience and vulnerability of different household types to poverty, offering insights into the factors that enable sustained escapes from poverty. The findings underscore the importance of targeted social protection strategies and policy interventions to support the poor and vulnerable, especially the near-poor, in improving their livelihood prospects and mitigating the impacts of various shocks. The study's comprehensive analysis provides valuable input for policymakers in formulating effective measures to address poverty and inequality in the Philippines.
Keywords: 330; panel data; poverty; near-poor